Islamic Resilience as Spiritual and Psychological Coping Strategies for Muslims during COVID-19 Pandemic - Gumiandari, Septi; Abd. Madjid,; Ilman Nafi’a,; Safii Safii,; Hidayat, Abas (Afkar: Jurnal Akidah dan Pemikiran Islam, 2022)
This study aims to explain the concept of resilience from the Islamic perspective. This study used qualitative methodology with a literature approach. The results showed that the phenomenon of religious human behavior should not only be judged by the lens of modern secular psychology theory, but also by the theory of psychology based on Islamic values. It is because they have different frames in looking at reality; and resilience in Islam is an obligation. Having resilient personalities, in Islamic teaching, means individuals’ iman (faith) should be tested. Humans are motivated to have resilience after getting life’s problems with the Covid-19 issue. Individuals’ faith has not reached a high level of spirituality when they have not been tested. There are some personalities in Islam that are in line with the concept of resilience for overcoming the Covid-19 issue in positive psychology such as sabr, tawakkal, shukr, rida, ikhlas and tawbah. In order to increase resilience in overcoming the Covid-19 issue, Sufis provide spiritual training such as takhalli, tahalli, and tajalli.